Finnish SMEs and the development of the innovative collaboration platform - Zafar, Afnan; Kantola, Jussi; Sivula, Ari; Kwegyir-Afful, Ebo; Lotchi, Kodjovi (The International Society for Professional Innovation Management (ISPIM), 2019)
Global patterns of innovative platforms for the collaboration of SMEs have resulted in the formation of SME ecosystems to connect with new markets. Finland is an innovative country, trying its best to form a national SME collaboration platform to later connect to global SME networks. The study investigates factors involved in the development of such collaborative platforms. First, the conceptual framework of collaborative platforms was synthesized from SME networking literature. Then 30 SMEs from Finland were surveyed and analysed by statistical tools. The results provided support for a conceptual framework in terms of a relationship between six factors and their impact on the development of the platform. An implication for managers is that if they are welcoming enough toward a collaborative platform, there will be better evaluation of the financial situation of the company.
Keywords: SMEs; Open innovation; Platform; small and medium-sized enterprises; Finland; fi=Tuotantotalous|en=Industrial Management|